Assessment of Knowledge, Practice, and Attitude about Silver Diamine Fluoride among Postgraduate Students in Pediatric Dentistry in Karnataka - Kempaiah Siddaiah Madhusudhan; Bhargavi R. Vojjala; Priya Subramaniam (Wolters Kluwer Medknow Publications, 2024)
Background Dental caries occurs as a result of phasic demineralization and remineralization of dental hard tissues. In recent years, minimal invasive dentistry (MID) has replaced conventional treatment procedures. As part of MID, silver diamine fluoride (SDF) is being used to manage dental caries. However, little research has explored how informed dental postgraduates are about SDF. Aim To determine the knowledge, practice, and attitude of dental postgraduate students regarding SDF. Materials and Methods A questionnaire containing a total of 25 questions was drafted and distributed through Google Forms to postgraduates studying in the Department of Pedodontics and Preventive Dentistry within the state of Karnataka. The Chi-square (χ2) test was used to statistically analyze the obtained data. Results A total of 165 responses were obtained. Among the participants, 94.5% reported that they were aware of SDF. However, majority of the respondents were not able to correctly answer the questions assessing knowledge. Knowledge was higher among 3rd year followed by 2nd and 1st years (P ≤ 0.001). Only 59.4% of the respondents stated that they use SDF in their patients. However, nearly all respondents stated that this survey encouraged them to improve their understanding of SDF. Conclusion Awareness about SDF among postgraduates treating pediatric patients is quite high. Knowledge with regard to few aspects of SDF use is lacking. The attitude among the participants was positive.